Kandungan Zat Gizi Dan Daya Terima Bisjaka Dengan Penambahan Sari Tepung Daun Katuk - Rodien Sasaka; Abdul Salam; Igde Narda Widiada; Made Darawati (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. Biscuits are bakery products made by baking dough made from wheat flour or substitution, oil or fat, with or without the addition of other foodstuffs and permissible food additives. Indonesia is a consuming country of big wheat flour. This can be seen from the needs of wheat in Indonesia from year to year increasing, until in 2013 reached 2.6 million metric tons per year or up about 1.08% compared to the year 2012 (Hidayat in Midlanda, 2014). One solution to solve the problem is to utilize the flour from local foodstuff to produce wheat flour. So far, many products in the market are in the form of breastfeeding capsules or milk milk, but biscuits are not available in the market yet. the purpose of this research is to know the properties of Organoleptic and Nutritional Content of Biscuits Biscuits with Various Addition of Fat Katuk Leaf Extract.Research Methods. The method used is experimental method with Completely Randomized Design consisting of 3 treatment levels.Research Result. The result of research conducted is the most preferred biscuit products is t1 with the addition of 5% katuk leaf essence. Bisjaka contains carbohydrates, fats, ash and protein in high category while for the water content of biscuits is low. However, all parameters have met the quality requirements of biscuits according to SNI No.01-2973-93. Consumer panel acceptance test as many as 35 people (67%) can accept and 10 people (33%) can not accept biscuit products. The marketing of biscuit biscuit products is done in Juring Village Neighborhood of Praya District, Central Lombok regency, which buy biscuit biscuits are lactating mothers and children, but many buy biscuit biscuit products are pregnant and lactating mothers.Conclusion. Bisjaka bikuit products replace katuk leaf flour and have an interest in supporting bisjaka color, smell and biscuit flavor with p <0.05.